2012
DOI: 10.1128/jb.06792-11
|View full text |Cite
|
Sign up to set email alerts
|

Autocatalytic Maturation of the Tat-Dependent Halophilic Subtilase Nep Produced by the Archaeon Natrialba magadii

Abstract: Halolysins are subtilisin-like extracellular proteases produced by haloarchaea that possess unique protein domains and are salt dependent for structural integrity and functionality. In contrast to bacterial subtilases, the maturation mechanism of halolysins has not been addressed. The halolysin Nep is secreted by the alkaliphilic haloarchaeon Natrialba magadii, and the recombinant active enzyme has been synthesized in Haloferax volcanii. Nep contains an N-terminal signal peptide with the typical Tat consensus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…Each of these halolysins is synthesized as a precursor containing a Tat signal peptide, an N‐terminal propeptide, a subtilisin‐like catalytic domain, and a C‐terminal extension (CTE). Mutation analyses of the Tat signal peptides of SptA and Nep have shown that these halolysins are Tat‐dependent substrates (Shi et al ., ; Ruiz et al ., ). Nep and SptC reportedly mature autocatalytically (Ruiz et al ., ; Zhang et al ., ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Each of these halolysins is synthesized as a precursor containing a Tat signal peptide, an N‐terminal propeptide, a subtilisin‐like catalytic domain, and a C‐terminal extension (CTE). Mutation analyses of the Tat signal peptides of SptA and Nep have shown that these halolysins are Tat‐dependent substrates (Shi et al ., ; Ruiz et al ., ). Nep and SptC reportedly mature autocatalytically (Ruiz et al ., ; Zhang et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Mutation analyses of the Tat signal peptides of SptA and Nep have shown that these halolysins are Tat‐dependent substrates (Shi et al ., ; Ruiz et al ., ). Nep and SptC reportedly mature autocatalytically (Ruiz et al ., ; Zhang et al ., ). These findings raise interesting questions about whether Tat‐dependent halolysins can be prematurely activated before translocation across the cytoplasmic membrane in a folded state and how haloarchaea minimize the risk of premature activation of halolysins and associated proteolytic damage to cellular proteins.…”
Section: Introductionmentioning
confidence: 97%
“…Although the PkdD of SptC and the CTEs of other halolysins (e.g., SptA and Nep) show no significant homology, they are predicted to adopt a similar ␤-jelly roll-like structure. The importance of the CTE to enzymatic activity has been reported for halolysins R4 (7), SptA (11), and Nep (10). The CTE of SptA assists enzymatic activity toward protein substrates rather than smallpeptide substrates by facilitating the binding of protein substrates for catalysis (11).…”
Section: Discussionmentioning
confidence: 99%
“…The mature forms of halolysins are composed of not only a highly conserved catalytic domain (ϳ60 to 80% identity) but also a CTE. The CTEs of the above-mentioned halolysins also share high sequence identity (ϳ40 to 70%) and are reportedly important for the stability and activity of R4 (7), SptA (11), and Nep (10). The attachment of an extension to the C terminus of the catalytic domain appears to be a common strategy employed by halolysins to adapt to hypersaline environments.…”
mentioning
confidence: 99%
See 1 more Smart Citation